Burlesquing "Otherness" in Nineteenth-Century American Theatre: The Image of the Indian in John Brougham’s Met-a-mora; or, The Last of the Pollywogs (1847) and Po-Ca-Hon-Tas; or, The Gentle Savage (1855). - Detsi-Diamanti, Zoe (American Studies, 2007)
On the 19th-century American stage, the call for a “romanticized” representation of the Indian was part of the national effort to produce an indigenous literature. The popularity of such Indian stereotypes as the resistant but rapidly vanishing Noble Savage Metamora and the acquiescent Indian Princess Pocahontas was sustained by a wider political ideology that sought to define the limits and character of a distinctly American national identity. However, the highly sentimentalized Indian stereotypes that dominated the American stage in the 1820s and 1830s gradually turned white Americans’ attention from the historical reality of the Indians, whose presence had long required political action, to the imaginative realm of myth and symbol. John Brougham, an Irish actor-playwright who immigrated to America in 1842, quickly captured the essential discrepancy in the perception of the Indian as image/fiction and the native as reality. With his two burlesques, Met-a-mora; or, The Last of the Pollywogs (1847) and Po-Ca-Hon-Tas; or, The Gentle Savage (1855), Brougham signaled the end of the serious Indian dramas of the 1820s and 1830s and awakened the American audience of the time into an awareness of the absurdly false images they had been seen for so long and the excessively sentimentalized acting style they had been applauding. Through their essentially humorous approach to the national image of the Indian, Brougham’s burlesques constitute a reliable register of the social, political, and cultural context of mid-19th-century American society. His Indian characters are rendered closer to the lower classes and satirize the dominant political ideology that offered white Americans a world vision and historical sense that blurred their perception of the interaction between myth and history, thus permitting them to celebrate the Indian-symbol while abusing the native.